Bioinformatics: Principles and Applications - Harshawardhan P Bal (Tata McGraw-Hill, 2005)
This book is about those fundamental tools and techniques that revolutionized biomedical research, and enable us today to perform biology in silico. The book uses an integrative approach to illustrate the use of these tools, and binds them together to create a coherent strategy to tackle the overwhelming problem of biological information overload. the book covers the core set of tools that have become indispensable to scientific discovery in the post-genome era, and also demonstrates how these tools can be integrated programmatically with BioPerl to be used in an enhanced, truly high throughput- biology on steroids- manner.